First Described Case of Group B Streptococcus Pelvic Abscess in a Patient with No Medical Comorbidities - Paul Tyan; Elias Abi-Khalil; Karthik Dwarki; Gaby Moawad (Case Reports in Obstetrics and Gynecology)
Background. Group B Streptococcus is an organism that commonly infects a wide range of hosts including infants in the first week of life, pregnant women, and older age adults as well as adults with underlying medical comorbidities. Case. Large pelvic abscess in a nonpregnant patient found to be caused by Group B Streptococcus was treated successfully with IR guided drainage and antibiotics. Conclusion. Though rare, GBS can still be a cause of invasive infection even in individuals who are nonpregnant and have no underlying comorbidities. Empiric antibiotic coverage for this organism should be kept in mind when treating an abscess.